2021
DOI: 10.18332/tpc/135516
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette and dual product use as an emerging health threat to the US military

Abstract: INTRODUCTION Cigarette and e-cigarette use are threats to the health and readiness of the US military. The study objective was to determine the prevalence and factors associated with e-cigarette, cigarette, and dual use among active duty service members (SMs). METHODS We used data from the 2015 Health Related Behaviors Survey-a crosssectional survey weighted to represent the US military (n=16699). Weighted prevalence and odds ratios assessed associations between risk factors and e-cigarette/cigarette use via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…The study also demonstrated Service members who screened ‘positive’ for hazardous drinking, had increased odds of being an e-cigarette user; aligning to published research for the U.S. adult population which indicated e-cigarette users were more likely to engage in hazardous drinking behavior compared to those who do not use e-cigarettes 29 . Results of this study also aligned to a June 2021 study which concluded that Service members who had a probable alcohol use disorder were at greater odd of using e-cigarettes 30 . Amongst specific Service branches, the highest tobacco users were found amongst active duty Army and Navy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The study also demonstrated Service members who screened ‘positive’ for hazardous drinking, had increased odds of being an e-cigarette user; aligning to published research for the U.S. adult population which indicated e-cigarette users were more likely to engage in hazardous drinking behavior compared to those who do not use e-cigarettes 29 . Results of this study also aligned to a June 2021 study which concluded that Service members who had a probable alcohol use disorder were at greater odd of using e-cigarettes 30 . Amongst specific Service branches, the highest tobacco users were found amongst active duty Army and Navy.…”
Section: Discussionsupporting
confidence: 82%
“…29 Results of this study also aligned to a June 2021 study which concluded that Service members who had a probable alcohol use disorder were at greater odd of using e-cigarettes. 30 Amongst specific Service branches, the highest tobacco users were found amongst active duty Army and Navy. The Army and Navy makes up largest percentage of the overall active duty force, approximately 20% and 14%, respectively and 85% of the Army are male.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these behaviors were seen to be quite common in this study, and e-cigarette use and dual products use have been noted to be increasing in the military population. 31 Mental health specialists should also consider these health behaviors as part of their mental health assessments and risk strati cation for suicide behaviors. All survey materials included the survey report control system license number: DD-HA(BE)2189.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking. Cigarette smoking has declined among service members over recent years, from 24% in 2011 to 13.8% in 2015 [24]. However, exposure to other potentially hazardous agents such as e-cigarettes (12.4%) and dual product use (4.7%) has increased [24].…”
Section: Particle Count Associations With Service Member Demographicsmentioning
confidence: 99%